Mineral concentration in citrus peel flours - Cruz Lima , Viviane da; Sampaio, Raquel Flôres; Correia, Laís Donata Bento; Raposo Júnior, Luiz; Barretto, Andrea Carla da Silva; Pereira, Thaise Mariá Tobal (Comunicata Scientiae, 2024)
Citrus fruits are known for their health benefits but managing processing waste is a challenge. Extracting bioactive compounds from these residues to create new products is promising, but mineral analysis is essential for food safety. The objective of this study was to analyze how the methodology for obtaining flour from sweet passion fruit peel, Tahiti lime, Murcott tangerine, and pearl pineapple influences the amounts of minerals Fe, Zn, Mn, Cu, Cr, and to determine the presence of these minerals in flours according to the defined limits. Maceration demonstrated a significant reduction in mineral content, such as iron, zinc, manganese, copper, and chromium, in the flours of lime and tangerine peels and passion fruit albedo. There was an increase in mineral levels after this process, such as zinc in passion fruit flavedo flour and manganese in tangerine and pineapple peels. Fe, Zn, Mn, Cu, Cr were respectively determined in 100g-1 in flours, from lime peel: 3,696mg; 1,273mg; 22,834mg, 0.422mg; 1104.945 μg; tangerine peel: 1,322mg; 2,560mg; 13,571mg; 0.236mg; passion fruit albedo: 8,596mg; 6,480mg; 76,003mg; 1,031mg; passion fruit flavedo 8,609mg; 3,363mg; 86,167mg; 2,317mg; in pineapple skin: 12,181mg; 0.704mg; 71,018mg; *mg; 2224.215 μg. Cr was not determined in the flours: albedo and flavedo from passion fruit, and tangerine and Cu from pineapple peel. Flours are sources of minerals but must be consumed with caution due to high quantities that can exceed the maximum tolerable intake limits.